Survival rate and mortality rate of oral cancer patients in oral and maxilloficial clinical sciences department, Faculty of Dentistry, University of Malaya: A retrospective study / Ahmad Fadhli Ahmad Badruddin - Ahmad Fadhli, Ahmad Badruddin (2019)
Introduction: There have been great strides in the advancement of surgery and oncology however there have not been much improvement in survival rates of oral cancer patients. Limited studies have been performed in identifying significant predictors of survival rate for oral cancer in Malaysia. Objectives: The aim of this study was to investigate and analyze the survival rate and mortality rate of oral cancer patients presented at Oral & Maxillofacial Clinical Sciences Department, University of Malaya (OMCS, UM). Methods: This is a retrospective study involving 166 oral cancer patients seen in OMCS, UM from 1st March 1994 until 28th April 2019. Data collected include socio-demographic and clinic-pathologic factors. Survival analysis was done using SPSS version 23.0. Univariate and multivariate analysis were performed using the Kaplan-Meier method and Cox proportional hazards regression modal respectively. Results: The overall 5-year survival rate of oral cancer patients was 36.1% with a mean survival time of 159 months. Significant factors that influenced survival of oral cancer patients in this study were anatomic site, stage, histologic type, receiving treatment and surgery. Stage, receiving treatment and surgery were independent prognostic factors of survival rate. Conclusion: The 5-year survival rate of oral cancer patients in OMCS, UM were comparable to the survival rate reported for developing countries. Advanced stage of oral cancer and not receiving any treatment particularly surgery contributed to poor survival of oral cancer patients.